Bridget Jones : mad about the boy - Fielding, Helen, 1958- (New ork Alfred A. Knopf, 2013)
Londonite Bridget Jones faces the challenges of maintaining sex appeal as the years roll by, the nightmares of drunken texting, the skinny jean, the disastrous e-mail cc, total lack of Twitter followers, and TVs that need ninety buttons and three remotes to simply turn on.
Born-again virgin -- Mad about the boy -- Descent into chaos -- The great tree.
Keywords: Jones, Bridget (Fictitious character) -- Fiction; Single women -- England -- London -- Fiction; London (England) -- Fiction; Chick lit; Diary fiction; Humorous fiction